Non-Integer order approximation of a PID-Type controller for boost converters - Sánchez, Allan G. S.; Pérez Pinal, Francisco J.; Rodríguez Licea, Martín A.; Posadas Castillo, Cornelio (Multidisciplinary Digital Publishing Institute, 2021)
In this work, the voltage regulation of a boost converter is addressed. A non-integer order PID controller is proposed to deal with the closed-loop instability of the system. The average linear model of the converter is obtained through small-signal approximation. The resulting average linear model is considered divided into minimum and normalized non-minimum phase parts. This approach allows us to design a controller for the minimum phase part of the system, excluding temporarily the non-minimum phase one. A fractional-order PID controller approximation is suggested for the minimum phase part of the system. The proposal for the realization of the electrical controller is described and its implementation is used to corroborate its effectiveness when regulating the output voltage in the boost converter. The fractional-order PID approximation achieves regulation of the output voltage in the boost converter by exhibiting the iso-damping property and using a single control loop, which confirmed its effectiveness in terms of controlling non-minimum phase/variable parameter systems.